Rose Aromatherapy Affects Blood Pressure in Menopausal Women - Mayasari Putri Ardela; Nara Lintan Mega Puspita; Raffiky Pinandia Sustamy; Barirah (Journal of Global Research in Public Health, 2022)
The health problem that often occurs in menopause is hypertension. One way of non-pharmacological treatment for lowering blood pressure can be done using rose aromatherapy.The purpose of this study was to determine the effect of rose aromatherapy on blood pressure in mother menopause at the Mojoroto sub-district, Kediri, East Java. The research design uses the pre experiments approach one group pretest-posttest design. The study population is menopausal mothers who have high blood pressure with some 40 people. Random Sampling technique in getting a sample of 28 people. Collecting data using primary data using observation sheets and the results analyzed using the Wilcoxon test. From the results of the research conducted shows that getting ρ value = 0.001, which means that the value of ρ <α so that H0 rejected H1 is accepted, meaning there is an effect of rose aromatherapy on blood pressure in the mother menopause.Rose aromatherapy proven its effect in lowering blood pressure in menopausal women. Aromatherapy can be made non-pharmacological handling in lowering blood pressure in the elderly.